Beyond Conversion Chemistry: Unlocking a Cooperative Solid-Solution–Capacitive Sodium-Storage Mechanism in Nickel Phosphide - Liu, Jiaqin; Wang, Tongzhen; Yang, Jie; Li, Yulei; Li, Zhaoqian; Cui, Jiewu; Yu, Yan; Wu, Yucheng (Nano-Micro Letters, 2026)
Nickel-rich nickel phosphide (Ni2P) has emerged as a promising sodium-ion battery anode owing to its high theoretical capacity and intrinsic electronic conductivity, yet its charge storage chemistry remains controversial and is often oversimplified as a conversion reaction. Herein, we design a freestanding Ni2P composite electrode composed of ultrasmall Ni2P nanocrystals embedded within a phosphorus-doped, graphene-like porous carbon matrix. Comprehensive in-situ and ex-situ analyses unequivocally demonstrate an interstitial solid-solution mechanism, wherein Na+ ions reversibly occupy lattice interstitials via (111)-oriented interplanar channels, inducing reversible lattice breathing without phase transformation. This bulk intercalation process is synergistically coupled with a substantial pseudocapacitive contribution, establishing a cooperative dual-mode storage mechanism. Benefiting from this solid-solution–capacitive chemistry, the electrode delivers a high reversible capacity (≈560 mAh g−1), outstanding rate capability (135 mAh g−1 at 10 A g−1), and exceptional long-term stability (263 mAh g−1 after 2000 cycles). When paired with a Na3V2(PO4)3@C cathode, the full cell achieves a high-energy density of 245 Wh kg−1. This work establishes solid-solution–capacitive coupling as a general paradigm for designing high-rate and durable sodium-ion battery anodes. Highlights: 1 A cooperative dual-mode sodium-storage mechanism, combining interstitial solid-solution intercalation and surface pseudocapacitance, is identified, diverging from the conventional conversion-dominated chemistry of nickel phosphides. 2 In-situ/ex-situ analyses provide direct evidence of reversible Na+ insertion into lattice interstitials through (111)-oriented interplanar channels, enabling low-strain lattice breathing without phase transformation. 3 The freestanding Ni2P composite electrode achieves exceptional performance, including high reversible capacity (≈560 mAh g−1), remarkable rate capability (135 mAh g−1 at 10 A g−1), and long-term stability over 2000 cycles.